Potentials of hydrogen economy in energy transition towards 2050 net zero emission agenda: Opportunities for Nigeria - Abubakar S. Sambo; Abdullahi Adamu (The Proceedings of the Nigerian Academy of Science)
The existing energy ecosystem that sustains economic activity around the world is heavily dependent on coal, oil, and natural gas. In fact, all fossil fuels combined accounted for over 84 per cent of total global energy use in 2019. Reducing the carbon footprint of energy is a driving force in energy transitions. Hydrogen is an energy carrier that can transform the fossil-fuel dependent economy into a hydrogen economy, which can provide an emissions-free fuel. Among the key uses of hydrogen is that it can increase renewable electricity market growth potentials substantially and broaden the reach of renewable solutions. However, changing global energy dynamics mean that resource-holders cannot assume that their oil resources will translate into reliable future revenues. Accelerated energy transitions would result in lower demand and prices for hydrocarbons can cut sharply into future revenues. This provides the need for countries such as Nigeria to tap from the economic opportunities in hydrogen economy in the face of dwindling oil revenue. Energy transitions are opening up new opportunities for a different set of strategic resources. Nigeria is a home to many of the mineral resources that are critical in driving global energy transitions. The rising demand for the minerals that can support global energy transitions offers an opportunity for minerals-rich country like Nigeria. The country’s energy future is not doomed: many pathways are possible, but effective policy choices can guide the country to a more inclusive and sustainable energy future and accelerate its economic and industrial development.